The Effect of Using Herringbone Technique (HT) and Numbered Head Together Technique (NHTT) for Elementary Students’ Reading Comprehension Skill - Nova Claudia Tampubolon; Arsen Nahum Pasaribu (Institut Agama Islam Negeri Palopo, 2022)
This research presents a research report on the using of applying Herringbone Technique and Numbered Head Together Technique for students reading skill at SD Kalam Kudus 2 Medan . The objective is to find out the effect of using Herringbone Technique and Numbered Head Together Technique on students reading skill. The subjects of the study were grade 3 students of SD Kalam Kudus. They were divided into three groups. The first and the second groups are (Experimental Group). They were taught by Herringbone Technique and Numbered Head Together Technique in reading recount text, while the third group (Control Group) was taught by Herringbone Technique and Numbered Head Together Technique. The technique of data analysis used t-test. In analyzing the data the mean of the students score for pre-test in experimental group one (Herringbone Technique) is 59.16 the mean of the students score for post-test in experimental group two is 91.83. The mean of the students score for pre-test in experimental group two (Numbered Head Together Technique) is 45 the mean of the students score for post-test in experimental group two is 69.16. The mean for pre-test in control group is 46.66, and the mean for post-test in control group two is 56.16. The conclusion is that the using of Herringbone Technique is more effective than Numbered Head Together Technique. It is suggested than teachers should apply this technique as one of technique to improve students’ comprehension in reading text.